The Role of Leadership in Implementing Effective Business Continuity Plans in UKMs - Edwin Jhonatan Panggabean (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This research aims to explore the role of leadership in the implementation of Business Continuity Plans (BCP) in Small and Medium Enterprises (SMEs) in Indonesia. The methodology used is a qualitative approach through case studies and in-depth interviews with SME leaders who have successfully implemented BCP. The main findings indicate that effective leadership, good communication, and employee training are key factors in the successful implementation of BCP. The implications of this research suggest that SME leaders need to adopt an inclusive and collaborative leadership style to enhance the effectiveness of their business continuity plans.